2022
DOI: 10.1098/rsbl.2022.0129
|View full text |Cite
|
Sign up to set email alerts
|

Systemic application of the transient receptor potential vanilloid-type 4 antagonist GSK2193874 induces tail vasodilation in a mouse model of thermoregulation

Abstract: In humans, skin is a primary thermoregulatory organ, with vasodilation leading to rapid body cooling, whereas in Rodentia the tail performs an analogous function. Many thermodetection mechanisms are likely to be involved including transient receptor potential vanilloid-type 4 (TRPV4), an ion channel with thermosensitive properties. Previous studies have shown that TRPV4 is a vasodilator by local action in blood vessels, so here, we investigated whether constitutive TRPV4 activity affects Mus muscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Several TRP channels are temperature sensitive ( Figure 8 ) and our results here confirm that Trpv4-like channels are present on PVN neurones; we have previously illustrated the expression profile of Trpv4 within the PVN using immunohistochemistry ( Feetham et al, 2015b ) and have shown that application of the selective Trpv4 agonist GSK1016790A decreased the firing rate of PVN neurones ( Feetham et al, 2015b ). At the whole animal level, we have shown that ICV injection of the Trpv4 inhibitor RN1734 prevents the effect of hypotonic ASCF on blood pressure ( Feetham et al, 2015a ) and centrally located Trpv4 channels may be responsible for the vasodilatory effect of systemic injection of a Trpv4 agonist ( O'Brien et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several TRP channels are temperature sensitive ( Figure 8 ) and our results here confirm that Trpv4-like channels are present on PVN neurones; we have previously illustrated the expression profile of Trpv4 within the PVN using immunohistochemistry ( Feetham et al, 2015b ) and have shown that application of the selective Trpv4 agonist GSK1016790A decreased the firing rate of PVN neurones ( Feetham et al, 2015b ). At the whole animal level, we have shown that ICV injection of the Trpv4 inhibitor RN1734 prevents the effect of hypotonic ASCF on blood pressure ( Feetham et al, 2015a ) and centrally located Trpv4 channels may be responsible for the vasodilatory effect of systemic injection of a Trpv4 agonist ( O'Brien et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that ICV injection of hypotonic artificial cerebrospinal fluid (ACSF) into CD1 mice decreased mean blood pressure, but not heart rate and this effect was abolished by treatment with the Trpv4 inhibitor RN1734 ( Feetham et al, 2015a ). In another recent study, we found that systemic administration of the highly selective lipid-soluble Trpv4 antagonist GSK2193874 resulted in tail blood-flow dynamics that were in-compatible with a local (vascular smooth muscle or endothelial cell) mechanism ( O'Brien et al, 2022 ). In light of the data reported here, we hypothesised that PVN Trpv4 ion channels also play a role in thermoregulation.…”
Section: Introductionmentioning
confidence: 92%